2005
DOI: 10.1126/science.1117950
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Equine Influenza Virus to Dogs

Abstract: Molecular and antigenic analyses of three influenza viruses isolated from outbreaks of severe respiratory disease in racing greyhounds revealed that they are closely related to H3N8 equine influenza virus. Phylogenetic analysis indicated that the canine influenza virus genomes form a monophyletic group, consistent with a single interspecies virus transfer. Molecular changes in the hemagglutinin suggested adaptive evolution in the new host. The etiologic role of this virus in respiratory disease was supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
684
0
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(708 citation statements)
references
References 23 publications
7
684
0
17
Order By: Relevance
“…In the case of CO, there was no more detectable CIV after March 2011, when the virus appears to have disappeared. In contrast, the FL humane shelter had much lower than expected CIV nasal shedding, given the fact that CIV first emerged in the state and previous FL shelter studies showed relatively higher prevalence 1. On the other hand, the humane shelter in SC had more than expected CIV nasal shedding, which can be attributed to a CIV outbreak during the first months of sample collection (Fig 1).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In the case of CO, there was no more detectable CIV after March 2011, when the virus appears to have disappeared. In contrast, the FL humane shelter had much lower than expected CIV nasal shedding, given the fact that CIV first emerged in the state and previous FL shelter studies showed relatively higher prevalence 1. On the other hand, the humane shelter in SC had more than expected CIV nasal shedding, which can be attributed to a CIV outbreak during the first months of sample collection (Fig 1).…”
Section: Resultsmentioning
confidence: 86%
“…Canine influenza virus (CIV) (H3N8) was first detected in Florida (FL) racing greyhounds in 2004 and quickly spread into New York (NY) and FL shelter dog populations 1. The transmission of influenza A viruses is thought to be by direct contact, deposition of infectious droplets (≥5 μm) on nasal or oral mucosa, or inhalation of infectious particles (<5 μm) 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission and subclinical infection of human and avian H3N2 (Houser & Heuschele 1980, Song et al 2008), equine H3N8 (Crawford et al 2005), avian H5N1 (Songserm et al 2006b) and the pandemic 2009 H1N1 (Damiani et al 2012) influenza virus strains to dogs have been documented. Serological evidence of naturally acquired infections caused by seasonal human H1N1 and H3N2 (Ali et al 2011), the pandemic 2009 H1N1 (Sponseller et al 2010, Ali et al 2011), and the avian H5N1 (Songserm et al 2006a) influenza virus strains in cats have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Two established lineages of H3 canine influenza virus (CIV) have been described, of equine‐origin and avian‐origin 1. An H3N8 equine influenza virus (EIV) initially caused outbreaks in racing greyhounds in the United States in 20042, 3; however, epidemiological and serological evidence indicated that an H3N8 equine virus introduction around 1999 was likely the ancestral strain of the H3N8 CIV in the United States 4, 5. While there was evidence of additional EIV transmission events into dogs in the United States,6 there was no evidence of sustained transmission of these other events, nor were there reports of CIV transfer back to horses or to humans 7.…”
Section: Introductionmentioning
confidence: 99%